Taking on the Bailiff Monopoly in Poland - Józefowicz, Krzysztof (World Bank, Washington, DC, 2012)
The 2005 Doing Business report rated Poland as one of the slowest judicial systems in the world. It took 1,000 days for a contract to be enforced through the courts, causing Poland to be ranked 140th of 145 countries in regard to the speed of courts. This poor ranking prompted the National Bank of Poland and the World Bank to draft a report, 'Poland: legal barriers to contract enforcement,' which contained recommendations designed to speed up court proceedings. One of the key recommendations of the report was to open the bailiff profession to more competition, so as to improve the service bailiffs delivered. Specifically, the report called for an expanded number of bailiffs, for creditors to have greater choice among those bailiffs, and for the deregulation of bailiff fees. After a change of government in 2005, a new team including the author headed the justice ministry. The author was receptive to new ideas, and the justice ministry endorsed the report, which provided the impetus for undertaking these reforms. The author suggested three changes: (a) the justice minister should be able to appoint more bailiffs without going through a complicated procedure; (b) bailiffs should be able to compete with each other regardless of their location; and (c) price flexibility should be introduced to bailiff fees.